Metode USG dan Waterfall Pada Perancangan Sistem Informasi Berbasis Website - Ginting, Lisa Melvi; Silitonga, Agnes Irene; Situmorang, Hasianna Nopina; Sinaga, Ferry Indra H; Simamora, Yoakim (LPPM UNIKA Santo Thomas, 2024)
The designed information system is expected to optimize the activities of an SME. The design of this information system is website-based. Website can make easier for customers and potential customers to make purchase product and get to know about product. Website also can be used for marketing. Waterfall method is used for design information system web-based. Waterfall method contains analysis requirement, design, implementation, testing, and maintenance. Requirement that have been analyzed then be designed. This research uses UML diagram in design process such us use case, activity diagram, sequence diagram, database diagram. The model that has been designed then implemented by using PHP and MySQL. The next stage is verification by user. Verification test to know if website run well. Testing is held by SME, this testing contain system testing and function testing. The final stage in the waterfall method is maintenance. The Urgency, Seriousness, Growth (USG) method is used to show the priority scale in determining problem issues in SMEs.